ChemInform Abstract: L‐Proline Derived Bifunctional Organocatalysts: Enantioselective Michael Addition of Dithiomalonates to trans‐β‐Nitroolefins. Issue 34 (4th August 2016) - Jin, Hui; Kim, Seung Tae; Hwang, Geum‐Sook; Ryu, Do Hyun
Abstract: The preparation of the catalysts is described as well as their highly effective use in the title reaction of aryl or alkyldithiomalonates with β‐aryl or alkyl substituted nitroolefins.